Analysis of mechanical properties of different volleyballs - Schneider, F.; MacDonald, K.; Reimer, D.; Melnyk, A. D.; Oxland, T. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
Concussions are becoming an increasingly important issue in sports, especially in an area like volleyball that, until recently, seemed less prone to such injuries. The purpose of this study was to determine the coefficient of restitution and basic mechanical properties of standardized volleyballs, including stiffness and hysteresis, dependent on different influencing factors. A drop test was performed to calculate the coefficient of restitution based on the time of flight of the ball between the first and second bounce. This was detected using a microphone with a sampling frequency of 44.1 kHz. To determine the mechanical properties, a materials testing machine applied a compression force until a deformation of 50 mm was achieved. These data were sampled with a frequency of 12.5 kHz. The results showed that the three analysed factors in this study, including the ball model, gauge pressure, and incident velocity, had a significant influence on the coefficient of restitution. Therefore, the amount of energy dissipation during an impact situation at low velocities was significantly different within the tested sample of official standardized volleyballs. The stiffness and hysteresis of the volleyballs also varied significantly. These basic mechanical findings raise an interesting question as to whether the investigated factors are appropriate to predict forces acting on the head during a high velocity collision (25-30 m/s), ultimately resulting in a risk of concussion.